Peran Keterampilan Berpikir Kreatif Terhadap Kemampuan Resiliensi Remaja - Fitri, Qawiyyan; Mutahara, Nurul; Maslina, Maslina; Ayu, Siska Putri (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2025)
This study examines the contribution of creative thinking skills to adolescent resilience through a qualitative literature review approach. Data were collected via systematic searches of academic databases (Google Scholar, PubMed, ERIC) using a combination of keywords such as “creative thinking,” “adolescent resilience,” and related terminology. The analysis reveals that Guilford's dimensions of creative thinking (divergent and convergent) are significantly associated with enhanced resilience through three primary mechanisms: (1) strengthening cognitive flexibility, (2) developing innovative problem-solving capacity, and (3) optimizing emotional expression. Further analysis identifies mediating factors (emotional intelligence, self-efficacy, problem-solving ability) and moderating factors (social support, school environment) that influence the strength of this relationship. These findings reinforce Rutter’s resilience theory postulating the adaptive role of creativity in adolescent stress management. The study concludes that implementing comprehensive creativity-based educational interventions, supported by a conducive environment, represents a potential strategy for resilience development.